Integrated gas diffusion electrode based on additive manufacturing, preparation method of integrated gas diffusion electrode and integrated PEM electrolytic water membrane electrode
Through the integrated molding of the bipolar plate, diffusion layer and catalytic layer of the membrane electrode through additive manufacturing technology, the complex problems of the existing membrane electrode preparation process are solved, and the membrane electrodes with high performance, stability and large-scale production are achieved, which promotes the commercial development of PEM electrolytic water.
Patent Information
- Application Number
- CN202510115387.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-02
AI Technical Summary
The existing membrane electrode preparation process is complex and difficult to be suitable for large-scale production.
The bipolar plate, diffusion layer and catalytic layer are integrated with additive manufacturing technology. Through the coordinated manufacturing of continuous laser and ultrafast laser, combined with the aerosol jetting process, the preparation of integrated gas diffusion electrodes and PEM electrolytic water film electrodes is realized.
The preparation process of membrane electrodes is simplified, the performance and stability of membrane electrodes are improved, the number, volume and weight of components are reduced, and the commercial development of PEM electrolytic water is promoted.
Smart Images

Figure CN119913542A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of membrane electrode technology, and in particular to an integrated gas diffusion electrode based on additive manufacturing and a preparation method thereof, and an integrated PEM water electrolysis membrane electrode. Background Art
[0002] With the increasing consumption of fossil fuels such as coal, oil, and natural gas, environmental pollution and global warming have prompted the research and development of clean energy and renewable energy to become the focus. Hydrogen has become the most promising alternative energy source due to its high calorific value and relatively pollution-free products. The main methods of hydrogen production currently include fossil fuel hydrogen production, water electrolysis hydrogen production, thermochemical hydrogen production, and photocatalytic hydrogen production.
[0003] Among them, proton exchange membrane (PEM) water electrolysis hydrogen production technology is a promising green hydrogen preparation technology with fast dynamic response speed and high energy conversion efficiency. It converts renewable energy power generation into hydrogen for storage and realizes the mutual conversion of electricity and hydrogen. It is an important link in the hydrogen energy industry.
[0004] The membrane electrode is the place where the PEM water electrolysis reaction occurs. It is mainly composed of metal end plates, bipolar plates, diffusion layers, anode and cathode catalyst layers and proton exchange membranes. It plays a key role in fuel cells, and its characteristics directly determine the performance output of water electrolysis.
[0005] At present, the processing of traditional membrane electrodes requires multiple steps and complex assembly processes, including bipolar plate flow channel engraving, catalyst spraying, membrane electrode assembly and membrane electrode adaptation. Therefore, the existing process steps for preparing membrane electrodes are relatively complicated and cannot be applied to future large-scale production. Summary of the invention
[0006] In order to improve the problem of relatively complicated process steps in the existing preparation of membrane electrodes, the present application provides an integrated gas diffusion electrode based on additive manufacturing and a preparation method thereof, and an integrated PEM water electrolysis membrane electrode.
[0007] In a first aspect, the present application provides an integrated gas diffusion electrode based on additive manufacturing, which adopts the following technical solution: An integrated gas diffusion electrode based on additive manufacturing includes a bipolar plate, a diffusion layer and a catalyst layer which are integrally formed using an additive manufacturing process, wherein the catalyst layer includes a metal catalyst layer and an alloy catalyst layer, and the metal catalyst layer is located between the diffusion layer and the alloy catalyst layer, and a gas flow channel for gas circulation is formed on the bipolar plate.
[0008] Optionally, a plurality of blockages are provided on the gas flow channel, and the cross-sectional shape of the blockages is semicircular, triangular or rectangular.
[0009] The present application can enhance the disturbance effect on the fluid by setting a block on the gas flow channel, promote the electrolytic cell to discharge oxygen and heat in time, and set a block at the bottom of the straight channel to change the movement direction of liquid water when flowing through the flow channel, and guide the water flow to the anode diffusion layer.
[0010] Optionally, the raw material for preparing the metal catalyst layer is metal powder, the raw material for preparing the alloy catalyst layer is alloy powder, and the main metal element in the alloy powder is the same as the metal element in the metal powder.
[0011] Since different metal elements have different electronic structures, the interaction between two or more metals at the interface in an alloy system can change their electronic structure and lattice structure, thereby affecting their physical and chemical properties. There is a metal synergy between alloys. In a chemical reaction or catalytic process, two or more metal elements interact with each other to jointly improve the overall catalytic performance or reaction efficiency. Therefore, the main metal element in the alloy powder is the same as the metal element in the metal powder.
[0012] Optionally, the metal powder is selected from one or more of metal Pt, metal Ir, metal Ru, metal Pd, and metal Mn; The alloy powder is selected from one or more of Pt-based alloy, Ir-based alloy, Ru-based alloy, Pd-based alloy and Mn-based alloy.
[0013] Optionally, the metal powder has a particle size of 15-40 μm.
[0014] Optionally, the alloy powder has a particle size of 20-50 μm.
[0015] Optionally, the bipolar plate has a thickness of 3-5 mm.
[0016] Optionally, the height of the gas flow channel is 1-3 mm.
[0017] Optionally, the ridge width of the gas flow channel is 0.5-2 mm.
[0018] Optionally, the diffusion layer has a thickness of 2-3 mm.
[0019] Optionally, the thickness of the metal catalyst layer is no more than 1 mm.
[0020] Optionally, the alloy catalyst layer has a thickness of 0.2-0.8 mm.
[0021] Optionally, the diffusion layer is a porous structure with a pore size of 10-50 μm and a porosity of 60-90%.
[0022] Optionally, the diffusion layer is made of metal titanium fiber, the fiber has a diameter of 3-5 μm and a fiber length of 15-35 μm.
[0023] In a second aspect, the present application provides a method for preparing an integrated gas diffusion electrode based on additive manufacturing, which adopts the following technical solution: A method for preparing an integrated gas diffusion electrode based on additive manufacturing comprises the following steps: Step S1: using a continuous laser to perform additive manufacturing of a bipolar plate and form a preset gas flow channel on the bipolar plate; Step S2: using a continuous laser to perform additive manufacturing of a diffusion layer on the surface of the bipolar plate; Step S3: using an ultrafast laser to perform additive manufacturing of a metal catalyst layer on the surface of the diffusion layer; Step S4: using ultrafast laser and aerosol jet technology to perform additive manufacturing of an alloy catalyst layer on the surface of the metal catalyst layer, thereby obtaining the integrated gas diffusion electrode.
[0024] The present application forms a gas flow channel on the bipolar plate while manufacturing the bipolar plate in an additive manufacturing manner, and can also integrally form a block, making the entire bipolar plate manufacturing process simple and quick.
[0025] The present application adopts continuous laser in the manufacture of bipolar plates and diffusion layers. Continuous laser forming has high efficiency, and its significant thermal effect can easily lead to large heat-affected zones and thick casting layers. It is suitable for the manufacture of macroscopic components, namely the construction of bipolar plates and the subsequent construction of large voids in the gradient-distributed metal structure diffusion layer.
[0026] This application uses aerosol jetting technology to assist ultrafast laser collaboration in additive manufacturing when preparing the alloy catalyst layer. Based on the aerosol in-situ delivery technology of timing control and multi-channel delivery system, the timed and quantitative delivery of various nanomaterials is guaranteed. The combination of the two can realize the hierarchical precision control and path adaptive planning technology of laser collaborative scanning and aerosol in-situ delivery, develop aerosol and ultrafast laser off-axis path collaborative scanning mode, design a path coupling solution algorithm and customize the scanning strategy, and realize efficient printing of the scanning path. Moreover, the combination of ultrafast laser collaborative powder bed melting and aerosol jetting can realize the functional structure macro-micro-nano cross-scale shape control additive manufacturing.
[0027] Optionally, the laser parameters in step S1 are specifically: scanning interval of 0.03-0.2 mm, scanning speed of 200-3000 mm / s, and power of 80-450 W.
[0028] Optionally, the laser parameters in step S2 are specifically: scanning interval of 0.1-0.8 mm, scanning speed of 600-1800 mm / s, and power of 40-300 W.
[0029] Optionally, the laser parameters in step S3 are specifically: scanning interval of 0.05-0.15 mm, scanning speed of 400-2000 mm / s, and power of 100-400 W.
[0030] Optionally, the laser parameters in step S4 are specifically: scanning spacing of 0.08-0.25 mm, scanning speed of 300-2500 mm / s, power of 150 to 500 W; The specific parameters of the aerosol spraying process are: carrier gas temperature of 450-600° C., carrier gas pressure of 5-6 MPa, spraying distance of 6-10 mm, and nozzle speed of 60-90 mm / min.
[0031] Optionally, the carrier gas used in the aerosol spraying process is nitrogen.
[0032] In a third aspect, the present application provides an integrated PEM water electrolysis membrane electrode based on additive manufacturing, which adopts the following technical solution: An integrated PEM water electrolysis membrane electrode based on additive manufacturing is made of a proton exchange membrane and the integrated gas diffusion electrode based on additive manufacturing.
[0033] In summary, the present application includes at least one of the following beneficial effects: 1. The present invention uses continuous laser-ultrafast laser to design an integrated GDE structure for the diffusion layer and the catalyst layer, and reduces mass transfer resistance and improves membrane electrode performance by controlling porosity, pore size and electrochemically active surface area. Different from traditional water electrolysis membrane electrodes, additive manufacturing integrated membrane electrodes eliminate the use of binders (Nafion, etc.), improve material transmission and increase conductivity, make the membrane electrode interface more tightly bonded, and improve component stability and membrane electrode life.
[0034] 2. This application can ensure the high performance of the membrane electrode while utilizing additive manufacturing technology to reduce the number of components, the volume and weight of the membrane electrode, and simplify the configuration, thereby promoting the commercial development of PEM water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a schematic diagram of a preparation process of an integrated gas diffusion electrode based on additive manufacturing according to an embodiment of the present application; Figure 2 This is a comparison chart of membrane electrode performance curves obtained for Examples 1-6 of the present application; Figure 3This is a comparison chart of membrane electrode performance curves obtained in Example 1 of the present application and Comparative Example 1; Figure 4 This is a comparison chart of membrane electrode performance curves obtained in Example 2 of the present application and Comparative Example 2; Figure 5 This is a comparison chart of membrane electrode performance curves obtained in Example 3 of the present application and Comparative Example 3; DETAILED DESCRIPTION The following will be combined with the embodiments of the present invention and the accompanying drawings to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The particle size of the titanium powder used in the following examples is 15-35 μm.
[0037] Example 1 Example 1 This example provides an integrated PEM water electrolysis membrane electrode based on additive manufacturing. First, an integrated gas diffusion electrode is prepared. Figure 1 , and its preparation method comprises the following steps: Step 1: Use titanium powder as the raw material, use continuous laser to perform additive manufacturing of bipolar plates and form a preset gas flow channel on the bipolar plates, the laser / electron beam scanning interval is 0.03mm, the scanning speed is 200mm / s, and the power is 80W. The thickness of the metal bipolar plate is controlled at 3mm, the flow channel height is 1mm, a semicircular block is set at the bottom of the flow channel, and the flow channel ridge width is 0.5mm.
[0038] Step 2: Use titanium fiber as the raw material, and use continuous laser to perform additive manufacturing of gradient porous metal diffusion layer on the surface of bipolar plate, with laser / electron beam scanning spacing of 0.3mm, scanning speed of 800mm / s, and power of 60W. The thickness of porous metal diffusion layer is controlled at 2mm, the pore size is 15μm, the porosity is 60%, the diameter of titanium fiber is 3μm, and the length of titanium fiber is 20μm.
[0039] Step 3: Using metal powder as the raw material, an ultrafast laser is used to perform additive manufacturing of a dense metal catalyst layer on the surface of the diffusion layer, with a laser / electron beam scanning spacing of 0.08 mm, a scanning speed of 500 mm / s, and a power of 250 W. The thickness of the dense metal catalyst layer is controlled at 0.6 mm. The raw material metal powder for manufacturing the functional layer is composed of metal Pt and metal Ir in equal proportions, and the powder particle size is 18 μm.
[0040] Step 4: Using alloy powder as raw material, ultrafast laser and aerosol jetting process are used to perform additive manufacturing of a uniform in-situ alloy catalyst layer on the surface of the metal catalyst layer. The laser / electron beam scanning spacing is 0.16 mm, the scanning speed is 550 mm / s, and the power is 200 W. The aerosol carrier gas temperature is 480 ° C, the carrier gas pressure is 5 MPa, the spraying distance is 6.5 mm, and the nozzle movement speed is 65 mm / min. The thickness of the in-situ alloy catalyst layer is 0.4 mm. The alloy catalytic functional layer is made of raw material alloy powder composed of Pt-based alloy and Ir-based alloy in equal proportions, and the powder particle size is 24 μm, so as to obtain an integrated gas diffusion electrode.
[0041] After the integrated gas diffusion electrode is manufactured, it is combined with a proton exchange membrane to prepare an integrated PEM water electrolysis membrane electrode through static pressure assembly for performance testing.
[0042] Example 2 Example 2 This example provides an integrated PEM water electrolysis membrane electrode based on additive manufacturing. First, an integrated gas diffusion electrode is prepared. Figure 1 , and its preparation method comprises the following steps: Step 1: Use titanium powder as the raw material, use continuous laser to perform additive manufacturing of bipolar plates and form preset gas flow channels on the bipolar plates. The laser / electron beam scanning interval is 0.08 mm, the scanning speed is 500 mm / s, and the power is 150 W. The thickness of the metal bipolar plate is controlled at 4 mm, the flow channel height is 2 mm, semicircular and triangular blocks are set at the bottom of the flow channel, and the flow channel ridge width is 1 mm.
[0043] Step 2: Use titanium fiber as the raw material, and use continuous laser to perform additive manufacturing of gradient porous metal diffusion layer on the surface of bipolar plate, with laser / electron beam scanning spacing of 0.5mm, scanning speed of 1200mm / s, and power of 180W. The thickness of porous metal diffusion layer is controlled at 2.4mm, the pore size is 20μm, the porosity is 65%, the diameter of titanium fiber is 4μm, and the length of titanium fiber is 25μm.
[0044] Step 3: Using metal powder as a manufacturing raw material, an ultrafast laser is used to perform additive manufacturing of a dense metal catalyst layer on the surface of the diffusion layer, with a laser / electron beam scanning spacing of 0.1 mm, a scanning speed of 800 mm / s, and a power of 350 W. The thickness of the dense metal catalyst layer is controlled at 0.8 mm, and the raw material metal powder for manufacturing the functional layer is composed of metal Pt, metal Ir, and metal Ru in equal proportions, and the powder particle size is 20 μm.
[0045] Step 4: Using alloy powder as raw material, using ultrafast laser and aerosol jet technology to perform additive manufacturing of a uniform in-situ alloy catalyst layer on the surface of the metal catalyst layer, the laser / electron beam scanning spacing is 0.25mm, the scanning speed is 1000mm / s, and the power is 400W. The aerosol carrier gas temperature is 550℃, the carrier gas pressure is 6MPa, the spraying distance is 8mm, and the nozzle movement speed is 80mm / min. The thickness of the in-situ alloy catalyst layer is 0.6mm. The alloy powder used to manufacture the alloy catalytic functional layer is composed of Pt-based alloy, Ir-based alloy, and Ru-based alloy in equal proportions, and the powder particle size is 35μm, so as to obtain an integrated gas diffusion electrode.
[0046] After the integrated gas diffusion electrode is manufactured, it is combined with a proton exchange membrane to prepare an integrated PEM water electrolysis membrane electrode through static pressure assembly for performance testing.
[0047] Example 3 Example 3 This example provides an integrated PEM water electrolysis membrane electrode based on additive manufacturing. First, an integrated gas diffusion electrode is prepared. Figure 1 , and its preparation method comprises the following steps: Step 1: Use titanium powder as the raw material, use continuous laser to perform additive manufacturing of bipolar plates and form preset gas flow channels on the bipolar plates. The laser / electron beam scanning interval is 0.15 mm, the scanning speed is 1200 mm / s, and the power is 270 W. The thickness of the metal bipolar plate is controlled at 3.5 mm, the flow channel height is 2.5 mm, a triangular block is set at the bottom of the flow channel, and the flow channel ridge width is 1.2 mm.
[0048] Step 2: Use titanium fiber as the raw material, and use continuous laser to perform additive manufacturing of gradient porous metal diffusion layer on the surface of bipolar plate, with laser / electron beam scanning spacing of 0.6mm, scanning speed of 1500mm / s, and power of 240W. The thickness of porous metal diffusion layer is controlled at 2.8mm, the pore size is 25μm, the porosity is 70%, the diameter of titanium fiber is 5μm, and the length of titanium fiber is 30μm.
[0049] Step 3: Using metal powder as a raw material, an ultrafast laser is used to perform additive manufacturing of a dense metal catalyst layer on the surface of the diffusion layer, with a laser / electron beam scanning spacing of 0.12 mm, a scanning speed of 1300 mm / s, and a power of 150 W. The thickness of the dense metal catalyst layer is controlled at 0.5 mm. The raw material metal powder for manufacturing the functional layer is composed of metal Pt and metal Ir in equal proportions, and the powder particle size is 15 μm.
[0050] Step 4: Using alloy powder as raw material, using ultrafast laser and aerosol jet technology to perform additive manufacturing of a uniform in-situ alloy catalyst layer on the surface of the metal catalyst layer, the laser / electron beam scanning spacing is 0.08mm, the scanning speed is 350mm / s, and the power is 350W. The aerosol carrier gas temperature is 500℃, the carrier gas pressure is 5.5MPa, the spraying distance is 7.5mm, and the nozzle movement speed is 70mm / min. The thickness of the in-situ alloy catalyst layer is 0.5mm. The alloy powder used to manufacture the alloy catalytic functional layer is composed of Pt-based alloy and Ir-based alloy in equal proportions, and the powder particle size is 20μm, so as to obtain an integrated gas diffusion electrode.
[0051] After the integrated gas diffusion electrode is manufactured, it is combined with a proton exchange membrane to prepare an integrated PEM water electrolysis membrane electrode through static pressure assembly for performance testing.
[0052] Example 4 Example 4 This example provides an integrated PEM water electrolysis membrane electrode based on additive manufacturing. First, an integrated gas diffusion electrode is prepared. Figure 1 , and its preparation method comprises the following steps: Step 1: Use titanium powder as the raw material, use continuous laser to perform additive manufacturing of bipolar plates and form a preset gas flow channel on the bipolar plates, the laser / electron beam scanning interval is 0.2mm, the scanning speed is 1800mm / s, and the power is 400W. The thickness of the metal bipolar plate is controlled at 5mm, the flow channel height is 3mm, a rectangular block is set at the bottom of the flow channel, and the flow channel ridge width is 2mm.
[0053] Step 2: Use titanium fiber as the raw material, and use continuous laser to perform additive manufacturing of gradient porous metal diffusion layer on the surface of bipolar plate, with laser / electron beam scanning spacing of 0.8mm, scanning speed of 1800mm / s, and power of 300W. The thickness of porous metal diffusion layer is controlled at 3mm, the pore size is 40μm, the porosity is 80%, the diameter of titanium fiber is 4.5μm, and the length of titanium fiber is 35μm.
[0054] Step 3: Using metal powder as a manufacturing raw material, an ultrafast laser is used to perform additive manufacturing of a dense metal catalyst layer on the surface of the diffusion layer, with a laser / electron beam scanning spacing of 0.15 mm, a scanning speed of 1600 mm / s, and a power of 400 W. The thickness of the dense metal catalyst layer is controlled at 1 mm, and the raw material metal powder for manufacturing the functional layer is composed of metal Pt, metal Ir, and metal Pd in equal proportions, and the powder particle size is 30 μm.
[0055] Step 4: Using alloy powder as raw material, using ultrafast laser and aerosol jet technology to perform additive manufacturing of a uniform in-situ alloy catalyst layer on the surface of the metal catalyst layer, the laser / electron beam scanning spacing is 0.2mm, the scanning speed is 1500mm / s, and the power is 500W. The aerosol carrier gas temperature is 550℃, the carrier gas pressure is 6MPa, the spraying distance is 9mm, and the nozzle movement speed is 75mm / min. The thickness of the in-situ alloy catalyst layer is 0.8mm. The alloy powder used to manufacture the alloy catalytic functional layer is composed of Pt-based alloy, Ir-based alloy, and Pd-based alloy in equal proportions, and the powder particle size is 40μm, so as to obtain an integrated gas diffusion electrode.
[0056] After the integrated gas diffusion electrode is manufactured, it is combined with a proton exchange membrane to prepare an integrated PEM water electrolysis membrane electrode through static pressure assembly for performance testing.
[0057] Example 5 Example 5 This example provides an integrated PEM water electrolysis membrane electrode based on additive manufacturing. First, an integrated gas diffusion electrode is prepared. Figure 1 , and its preparation method comprises the following steps: Step 1: Use titanium powder as the raw material, use continuous laser to perform additive manufacturing of bipolar plates and form preset gas flow channels on the bipolar plates. The laser / electron beam scanning interval is 0.12 mm, the scanning speed is 2500 mm / s, and the power is 450 W. The thickness of the metal bipolar plate is controlled at 4.5 mm, the flow channel height is 1.5 mm, alternating triangular and rectangular blocks are set at the bottom of the flow channel, and the flow channel ridge width is 1.5 mm.
[0058] Step 2: Use titanium fiber as the raw material, and use continuous laser to perform additive manufacturing of gradient porous metal diffusion layer on the surface of bipolar plate, with laser / electron beam scanning spacing of 0.1mm, scanning speed of 600mm / s, and power of 40W. The thickness of porous metal diffusion layer is controlled at 2mm, the pore size is 10μm, the porosity is 60%, the diameter of titanium fiber is 3.5μm, and the length of titanium fiber is 15μm.
[0059] Step 3: Using metal powder as the raw material, an ultrafast laser is used to perform additive manufacturing of a dense metal catalyst layer on the surface of the diffusion layer, with a laser / electron beam scanning spacing of 0.05 mm, a scanning speed of 400 mm / s, and a power of 100 W. The thickness of the dense metal catalyst layer is controlled at 0.4 mm. The raw material metal powder for manufacturing the functional layer is composed of metal Pt, metal Ir, and metal Mn in equal proportions, and the powder particle size is 40 μm.
[0060] Step 4: Using alloy powder as raw material, using ultrafast laser and aerosol jet process to perform additive manufacturing of uniform in-situ alloy catalyst layer on the surface of metal catalyst layer, the laser / electron beam scanning spacing is 0.25mm, the scanning speed is 2500mm / s, and the power is 450W. The aerosol carrier gas temperature is 450℃, the carrier gas pressure is 5MPa, the spraying distance is 10mm, and the nozzle movement speed is 90mm / min. The thickness of the in-situ alloy catalyst layer is 0.2mm. The alloy powder of raw materials for manufacturing the alloy catalytic functional layer is composed of Pt-based alloy, Ir-based alloy, and Mn-based alloy in equal proportions, and the powder particle size is 50μm, so as to obtain an integrated gas diffusion electrode.
[0061] After the integrated gas diffusion electrode is manufactured, it is combined with a proton exchange membrane to prepare an integrated PEM water electrolysis membrane electrode through static pressure assembly for performance testing.
[0062] Example 6 Example 6 This example provides an integrated PEM water electrolysis membrane electrode based on additive manufacturing. First, an integrated gas diffusion electrode is prepared. Figure 1 , and its preparation method comprises the following steps: Step 1: Use titanium powder as the raw material, use continuous laser to perform additive manufacturing of bipolar plates and form preset gas flow channels on the bipolar plates. The laser / electron beam scanning interval is 0.2 mm, the scanning speed is 3000 mm / s, and the power is 350 W. The thickness of the metal bipolar plate is controlled at 5 mm, the flow channel height is 2.5 mm, semicircular, triangular and rectangular blocks are set at the bottom of the flow channel, and the flow channel ridge width is 2 mm.
[0063] Step 2: Use titanium fiber as the raw material, and use continuous laser to perform additive manufacturing of gradient porous metal diffusion layer on the surface of bipolar plate, with laser / electron beam scanning spacing of 0.6mm, scanning speed of 1500mm / s, and power of 250W. The thickness of porous metal diffusion layer is controlled at 2.5mm, the pore size is 50μm, the porosity is 90%, the diameter of titanium fiber is 4μm, and the length of titanium fiber is 25μm.
[0064] Step 3: Using metal powder as a raw material, an ultrafast laser is used to perform additive manufacturing of a dense metal catalyst layer on the surface of the diffusion layer, with a laser / electron beam scanning spacing of 0.12 mm, a scanning speed of 2000 mm / s, and a power of 300 W. The thickness of the dense metal catalyst layer is controlled at 0.6 mm, and the raw material metal powder for manufacturing the functional layer is composed of metal Ir and metal Ru in equal proportions, and the powder particle size is 25 μm.
[0065] Step 4: Using alloy powder as raw material, using ultrafast laser and aerosol jet technology to perform additive manufacturing of a uniform in-situ alloy catalyst layer on the surface of the metal catalyst layer, the laser / electron beam scanning spacing is 0.2mm, the scanning speed is 2000mm / s, and the power is 150W. The aerosol carrier gas temperature is 600℃, the carrier gas pressure is 5MPa, the spraying distance is 6mm, and the nozzle movement speed is 60mm / min. The thickness of the in-situ alloy catalyst layer is 0.6mm. The alloy catalytic functional layer is made of raw material alloy powder composed of Ir-based alloy and Ru-based alloy in equal proportions, and the powder particle size is 30μm, so as to obtain an integrated gas diffusion electrode.
[0066] After the integrated gas diffusion electrode is manufactured, it is combined with a proton exchange membrane to prepare an integrated PEM water electrolysis membrane electrode through static pressure assembly for performance testing.
[0067] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that the bipolar plate and diffusion layer of Comparative Example 1 are purchased, wherein the bipolar plate is purchased from the titanium bipolar plate of Guangzhou Songteng Hydrogen Energy Technology Co., Ltd.; and the diffusion layer is purchased from the porous gas diffusion layer of Sichuan Boersmai Technology Co., Ltd. The preparation method is as follows: First, additive manufacturing of the metal catalyst layer (same as step S3 in Example 1) and additive manufacturing of the alloy catalyst layer (same as step S4 in Example 1) are performed on the proton exchange membrane, and then an integrated PEM water electrolysis membrane electrode is prepared by static pressure assembly with the purchased diffusion layer and bipolar plate for performance testing.
[0068] Comparative Example 2 Comparative Example 2 is substantially the same as Example 2, except that the metal catalyst layer and the alloy catalyst layer in Comparative Example 2 are both prepared by ultrasonic spraying. The specific preparation method is as follows: First, additive manufacturing of the bipolar plate (same as step S1 in Example 2) and additive manufacturing of the diffusion layer (same as step S2 in Example 2) are performed, and then a catalytic layer is prepared on the surface of the proton exchange membrane by ultrasonic spraying of the catalyst (the total metal loading is consistent with that in Example 2). Finally, the two are matched and an integrated PEM water electrolysis membrane electrode is prepared by static pressure assembly for performance testing.
[0069] Comparative Example 3 Comparative Example 3 is basically the same as Example 3, except that the bipolar plate and diffusion layer of Comparative Example 3 are purchased, and the metal catalyst layer and the alloy catalyst layer are prepared by ultrasonic spraying, wherein the bipolar plate is purchased from the titanium bipolar plate of Guangzhou Songteng Hydrogen Energy Technology Co., Ltd.; and the diffusion layer is purchased from the porous gas diffusion layer of Sichuan Boersmai Technology Co., Ltd. The preparation method is as follows: First, the metal catalyst layer and the alloy catalyst layer were prepared on the proton exchange membrane by ultrasonic spraying of catalyst, and then the purchased diffusion layer and bipolar plate were matched, and the integrated PEM water electrolysis membrane electrode was prepared by static pressure assembly for performance testing.
[0070] Figure 2 This is a comparison chart of membrane electrode performance curves obtained in Examples 1-6 of this application. Figure 2 It can be seen that different technical solutions (including laser parameter setting, flow channel design, and catalyst layer metal selection, etc.) will have different effects on the performance of membrane electrode samples. While ensuring superior low-electricity density activity, the high-electricity density mass transfer efficiency will be reduced, and the energy consumption will be high; while ensuring sufficient mass transfer efficiency, the low-electricity density initial activity is poor. Therefore, it is necessary to determine a suitable technical solution to improve the transmission capacity of protons, gas phases, and liquid phases at the three-phase interface, increase the membrane electrode area, and optimize the structure of the membrane electrode to ensure more efficient catalytic activity and mass transfer capacity. At the same time, additive manufacturing can optimize the electrolyzer flow channel design, component assembly process, and reduce the number of parts, making the electrolyzer structure more compact, reducing the contact resistance between components, maximizing the power density of the electrolyzer, and reducing unit power consumption.
[0071] The difference between Comparative Example 1 and Example 1 is that the bipolar plate and diffusion layer of the sample are not additively manufactured. The difference between Comparative Example 2 and Example 2 is that the metal catalyst layer and alloy catalyst layer of the sample are both ultrasonically sprayed and non-additively manufactured. The difference between Comparative Example 3 and Example 3 is that the bipolar plate and diffusion layer of the sample are not additively manufactured, and the metal catalyst layer and alloy catalyst layer of the sample are both ultrasonically sprayed and non-additively manufactured. Figure 3-Figure 5 From the performance comparison, it can be seen that the performance gap between the comparative example and the embodiment in the low electric density area is relatively small. With the improvement of electric density, the gap increases. The main reason for the analysis is that the new macro-micro-nano cross-scale integrated manufacturing process of aerosol-assisted continuous laser-ultrafast laser coordinated multi-level reaction functional structure can be used for gradient porous electrodes. The layer-by-layer printing idea is adopted. Continuous laser additive molding is performed in a single layer, and multi-active metal nanoparticles are delivered in situ along the molding contour by high-precision mode aerosol jet technology. The ultrafast laser hierarchical regulation ability is used to realize the in-situ alloying of multi-incompatible metals to form a gradient porous electrode with high-quality in-situ high-entropy alloy activity. At the same time, considering the mass transfer efficiency, additive manufacturing optimizes the bipolar plate flow channel structure and the porous structure of the diffusion layer in the electrolyzer, promotes the release of oxygen in the diffusion layer, reduces the local accumulation of oxygen in the diffusion layer, promotes sufficient water to pass through the diffusion layer to the catalytic layer for electrolysis of water, reduces the mass transfer resistance inside the electrolyzer under high working current density, enhances the heat transfer process in the electrolyzer, reduces the voltage loss of the electrolyzer, and improves the electrolysis efficiency.
[0072] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. An integrated gas diffusion electrode based on additive manufacturing, characterized in that: It includes a bipolar plate, a diffusion layer and a catalyst layer which are integrally formed by an additive manufacturing process. The catalyst layer includes a metal catalyst layer and an alloy catalyst layer, and the metal catalyst layer is located between the diffusion layer and the alloy catalyst layer. A gas flow channel for gas circulation is formed on the bipolar plate.
2. The integrated gas diffusion electrode based on additive manufacturing according to claim 1, characterized in that: A plurality of blocking blocks are arranged on the gas flow channel, and the cross-sectional shape of the blocking blocks is semicircular, triangular or rectangular.
3. The integrated gas diffusion electrode based on additive manufacturing according to claim 1, characterized in that: The raw material for preparing the metal catalyst layer is metal powder, and the raw material for preparing the alloy catalyst layer is alloy powder, and the main metal element in the alloy powder is the same as the metal element in the metal powder.
4. The integrated gas diffusion electrode based on additive manufacturing according to claim 3, characterized in that: The metal powder is selected from one or more of metal Pt, metal Ir, metal Ru, metal Pd, and metal Mn; The alloy powder is selected from one or more of Pt-based alloy, Ir-based alloy, Ru-based alloy, Pd-based alloy and Mn-based alloy.
5. The method for preparing an integrated gas diffusion electrode based on additive manufacturing according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step S1: using a continuous laser to perform additive manufacturing of a bipolar plate and form a preset gas flow channel on the bipolar plate; Step S2: using a continuous laser to perform additive manufacturing of a diffusion layer on the surface of the bipolar plate; Step S3: using an ultrafast laser to perform additive manufacturing of a metal catalyst layer on the surface of the diffusion layer; Step S4: using ultrafast laser and aerosol jet technology to perform additive manufacturing of an alloy catalyst layer on the surface of the metal catalyst layer, thereby obtaining the integrated gas diffusion electrode.
6. The method for preparing an integrated gas diffusion electrode based on additive manufacturing according to claim 5, characterized in that: The laser parameters in step S1 are specifically: scanning interval of 0.03-0.2 mm, scanning speed of 200-3000 mm / s, and power of 80-450 W.
7. The method for preparing an integrated gas diffusion electrode based on additive manufacturing according to claim 5, characterized in that: The laser parameters in step S2 are specifically: scanning interval of 0.1-0.8 mm, scanning speed of 600-1800 mm / s, and power of 40-300 W.
8. The method for preparing an integrated gas diffusion electrode based on additive manufacturing according to claim 5, characterized in that: The laser parameters in step S3 are specifically: scanning interval of 0.05-0.15 mm, scanning speed of 400-2000 mm / s, and power of 100-400 W.
9. The method for preparing an integrated gas diffusion electrode based on additive manufacturing according to claim 5, characterized in that: The laser parameters in step S4 are specifically: scanning spacing of 0.08-0.25 mm, scanning speed of 300-2500 mm / s, and power of 150 to 500 W; The specific parameters of the aerosol spraying process are: carrier gas temperature of 450-600° C., carrier gas pressure of 5-6 MPa, spraying distance of 6-10 mm, and nozzle speed of 60-90 mm / min.
10. An integrated PEM water electrolysis membrane electrode based on additive manufacturing, characterized in that: It is made of a proton exchange membrane and an integrated gas diffusion electrode based on additive manufacturing as described in any one of claims 1 to 4.
Citation Information
Cited By
Laser solid-phase in-situ constructed integrated membrane electrode and preparation method thereof
CN121161329A